2006
DOI: 10.1021/ie050885t
|View full text |Cite
|
Sign up to set email alerts
|

NOx-Mediated Homogeneous Pathways for the Synthesis of Formaldehyde from CH4−O2 Mixtures

Abstract: A detailed kinetic network for homogeneous CH 4 -O 2 -NO x reactions is used to estimate maximum attainable formaldehyde (and methanol) yields and to identify elementary steps that lead to the observed enhancement effects of NO x on CH 4 oxidation rates, to HCHO yield limits, and to NO x losses to unreactive N-compounds. NO x was shown previously to increase CH 4 oxidation rates and HCHO yields in CH 4 -O 2 reactions, but maximum yields were low (<10%) and intrinsic kinetic limits were not rigorously examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 51 publications
5
33
0
Order By: Relevance
“…21 This ratio increases as the RH products become more stable (R + H → RH, more exothermic). These abstraction reactions become less sensitive (${k{{{\rm R}\hfill \atop {\rm CH}{_{4}}\hfill}}}$ /${k{{R\hfill \atop {\rm C}{_{2}}{\rm H}{_{6}}\hfill}}}$ is larger) to differences in energy between the CH bonds in CH 4 and C 2 H 6 (CH 4 : 439 kJ mol −1 ; C 2 H 6 : 423 kJ mol −1 )20 as the abstraction products become more stable, as is also the case for the relative rates of HCHO and CH 4 oxidation via homogeneous pathways 22. OH radicals lead to very exothermic H‐abstraction reactions and to the highest ${k{{{\rm R}\hfill \atop {\rm CH}{_{4}}\hfill}}}$ /${k{{R\hfill \atop {\rm C}{_{2}}{\rm H}{_{6}}\hfill}}}$ ratios (Figure 3).…”
Section: Methodsmentioning
confidence: 94%
“…21 This ratio increases as the RH products become more stable (R + H → RH, more exothermic). These abstraction reactions become less sensitive (${k{{{\rm R}\hfill \atop {\rm CH}{_{4}}\hfill}}}$ /${k{{R\hfill \atop {\rm C}{_{2}}{\rm H}{_{6}}\hfill}}}$ is larger) to differences in energy between the CH bonds in CH 4 and C 2 H 6 (CH 4 : 439 kJ mol −1 ; C 2 H 6 : 423 kJ mol −1 )20 as the abstraction products become more stable, as is also the case for the relative rates of HCHO and CH 4 oxidation via homogeneous pathways 22. OH radicals lead to very exothermic H‐abstraction reactions and to the highest ${k{{{\rm R}\hfill \atop {\rm CH}{_{4}}\hfill}}}$ /${k{{R\hfill \atop {\rm C}{_{2}}{\rm H}{_{6}}\hfill}}}$ ratios (Figure 3).…”
Section: Methodsmentioning
confidence: 94%
“…NO oxidation also plays a significant role in NO x -mediated homogenous pathways of CH 4 oxidation to produce formaldehyde (HCHO). Iglesia and coworkers [18] have shown that CH 4 -O 2 mixtures in the presence of NO x , particularly NO 2 , exhibit significant reaction rates increases and HCHO yield. Lastly, NO oxidation is part of nitric acid synthesis via the Ostwald process (eq.…”
Section: [ 1 7 ] H a V E R E C E N T L Y S H O W N T H A T N O O X I mentioning
confidence: 99%
“…We have previously shown that reactions with energetic H-abstractors, such as OH radicals, react less selectively with the weaker C-H bonds in HCHO (relative to stronger C-H bonds in CH 4 ) than more stable radicals, such as O and HO 2 . 40 OH radicals are among the most thermodynamically unstable and reactive H-abstractors; they form very strong O-H bonds within the stable H 2 O molecules formed in such processes. 18 The ratio of the rate constants for H-abstraction from ethane and methane by gas-phase OH radicals (k C 2 H 6 OH /k CH 4 OH ) is 3.3-4.4.…”
Section: H 2 O-mediated C-h Bond Activation Pathwaysmentioning
confidence: 99%